ANÁLISIS E INTERPRETACIÓN DE LAS RASTRILLADAS INDÍGENAS DEL SECTOR CENTRO-ESTE DE LA PROVINCIA DE LA PAMPA - Rafael Pedro Curtoni (Revista de Arqueología Histórica Argentina y Latinoamericana, 2007)
In this paper, the 19th century network of indigenous roads, known as rastrilladas,is analysed. Also, two different ways of using the landscape, generated by Rankülchesand Salineros groups, are discussed. The analysis has been carried out consideringhistorical information and also through different fieldwork. In this way, it was possibleto recognise and record different kinds of rastrilladas, ranging from those consideredas principal to those characterised as secondary routes.